Pengalaman Dilema Etik Bagi Perawat di Ruang Intensive Care Unit - Sri Wulan Megawati; Anastasia Anna (Jurnal Medika Cendikia, 2018)
Nurses in Intensive Care (ICU) often face ethical dilemmas. They often face problems that require consideration of ethics in everyday practice. Advances in technology and consumer demand for high-quality services can put a nurse in a condition that causes a dilemma. The purpose of this research paper is to find out how ICU nurses experience in dealing with ethical dilemmas. The data collected in the form of publication of the journal literature, traced by-CINALHL EBSCOhost, ProQuest, PubMed, HealthMed Journal etc. by using the keyword "Ethical Dilemma", "Critical Care Nurse". At the end of 15 journals found at the top of the 2000s, between 2001- 2011. In general, the results of all the literature that in the review illustrates that the ethical dilemmas experienced by ICU nurses interpreted as how to choose between the two options and troubleshooting are not no solution. Cases are often faced ICU nurses are related decisions End of Life Care. Ethical dilemmas faced in general cause moral distress in nurses. To solve the problem of ethical dilemma discussions nurse team or talk with fellow nurses. Many obstacles faced by nurses in facing ethical dilemmas include the work environment is considered as a barrier in implementing the practice of ethics, both nurses tend conventionally grounded instead of using creativity and critical reflection, and three nurses difficulty applying ethical decisions in the context of a more challenging. The conclusion of this literature review, the findings of this study provide important information about the ethical dilemmas experienced by nurses. This information can be used as a baseline to improve ethical decision-making skills of nurses